2021
DOI: 10.1007/s40843-021-1689-4
|View full text |Cite
|
Sign up to set email alerts
|

In-situ electropolymerized bipolar organic cathode for stable and high-rate lithium-ion batteries

Abstract: To address the dissolution issue and enhance the electrochemical performance of organic electrode materials, herein, a bipolar organic cathode was prepared by in-situ electropolymerization of amino-phenyl carbazole naphthalene diimide (APCNDI). APCNDI is composed of n-type 1,4,5,8naphthalene tetracarboxylic diimide that stores Li cations and p-type carbazole groups which react with anions and serve as polymerization sites. Electropolymerization completely eliminated the dissolution problem of APCNDI, and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The rising demand for distributed and portable energy storage systems has been fueling the growth of rechargeable batteries [1][2][3][4][5]. Metal batteries, powered by metal stripping and plating, have been passionately focused upon, as they are capable of offering specific energy much higher than their rechargeable ion counterparts [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The rising demand for distributed and portable energy storage systems has been fueling the growth of rechargeable batteries [1][2][3][4][5]. Metal batteries, powered by metal stripping and plating, have been passionately focused upon, as they are capable of offering specific energy much higher than their rechargeable ion counterparts [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen and nitrogen atoms in organic materials are often serve as redox active centers in organic batteries. However, according to previous works, 41,50 the discharge voltage platform of the carbonyls in the benzene-based imide units was below 2.5 V and the nitrogen atoms in the imide rings were not activated even at high voltages up to 4.4 V. Thus, as shown in Fig. 3a, the nitrogen atoms from the TPPDA units were speculated as active sites in the TPPDA-PICOF.…”
Section: Resultsmentioning
confidence: 75%
“…[15,18,27,39,16] New peaks COLi and LiO centered at 1387 and 1060 cm −1 appeared, respectively, which is mainly attributed to the lithiation of CO and the formation of SEI films. [40][41][42] It is demonstrated that the insertion of Li + into CO results in the formation of COLi bond. [43] In addition, a small peak of sp 2 -hybridized carbon (1500-1400 cm −1 ) appeared in such initial discharging process.…”
Section: Ex Situ Spectroscopic Characterizations Of Redox Reactions O...mentioning
confidence: 99%